Does dexmedetomidine given as a premedication or intraoperatively reduce post-hospitalisation behaviour change in children? A study protocol for a randomised controlled trial in a tertiary paediatric hospital. Issue 4 (17th April 2018) - Lee-Archer, Paul; McBride, Craig; Paterson, Rebecca; Reade, Michael; Regli-von Ungern-Sternberg, Britta; Long, Deborah
Abstract : Introduction: It has been reported that post-hospitalisation behaviour change (PHBC) occurs in over 50% of children undergoing a general anaesthetic and manifests as behaviours such as sleep and eating disorders, defiance of authority, nightmares, enuresis and temper tantrums. The effect is usually short-lived (2–4 weeks); however, in 5–10% of children, these behaviours can last up to 12 months. The risk factors for developing PHBC include underlying anxiety in the child or parent, a previous bad hospital experience, emergence delirium and preschool age. A recent meta-analysis of alpha-2 agonists (including dexmedetomidine) found that they effectively reduce the incidence of emergence delirium but none of the studies looked at longer term outcomes, such as PHBC. Methods and analysis: Two-year-old to seven-year-old children requiring general anaesthesia for common day-case procedures will be randomly assigned to one of three groups: a dexmedetomidine pre medication group, an intraoperative dexmedetomidine group and a control group. Baseline anxiety levels of the parent will be recorded and the anxiety of the child during induction of anaesthesia will also be recorded using validated tools. The primary outcome will be negative behaviours after hospitalisation and these will be measured using the Post Hospitalisation Behaviour Questionnaire for Ambulatory Surgery and the Strengths and Difficulties Questionnaire. These questionnaires will be administered by a blinded researcher at days 3, 14 and 28 post surgery. Ethics and dissemination: Ethics approval has been granted by the Children's Health Queensland human research ethics committee (HREC/15/QRCH/248) and the University of Queensland human research ethics office (#2016001715). Any amendments to this protocol will be submitted to the ethics committees for approval. Trial registration number: ANZCTR:12616000096459; Pre-results .